Metaphor and translation - Trim, Richard, 1950-; Śliwa, Dorota (Cambridge Scholars Publisher, 2019)
This volume brings together the ideas put forward at an international conference on Metaphor and Translation held at the University of Toulon, France, in June 2017. The bilingual nature of the contributions here provides an insight into recent linguistic theories from both the English- and French-speaking worlds. This diversified approach is further enhanced by contributors being based in a large number of countries worldwide and working on different language combinations. The kinds of problem areas investigated here include a wide range of themes. They cover aspects ranging from methodological.